2014
DOI: 10.1111/bjh.12909
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with relapsed or refractory multiple myeloma in a phase I study of everolimus in combination with lenalidomide

Abstract: SummaryEverolimus, an oral mammalian target of rapamycin (mTOR) inhibitor, has been studied in multiple myeloma (MM) but lacks significant single agent activity. Based on preclinical studies showing synergistic activity of mTOR inhibitors with lenalidomide, we studied the combination of lenalidomide and everolimus in relapsed or refractory MM in a phase I clinical trial. We assessed patient samples using gene expression, Western blotting and immunohistochemistry to probe the mTOR pathway. Twenty-six patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…47 Recently, based on in vitro synergism, 48 the combination of everolimus and lenalidomide was explored in a phase I trial and was found to have promising activity and acceptable tolerability in patients with relapsed MM. 49 Interestingly, weekly bortezomib combined with temsirolimus showed promising activity in relapsed MM, with responses in patients who had been refractory to prior bortezomib-containing regimens. 50 Since everolimus as a single agent showed promising activity, with a limited rate of side effects, in relapsed and/or refractory MM patients, efforts should be made to evaluate optimal combination partners to enhance the anti-myeloma activity and to target the PI3K-AKT-mToR signaling network at multiple sites.…”
mentioning
confidence: 99%
“…47 Recently, based on in vitro synergism, 48 the combination of everolimus and lenalidomide was explored in a phase I trial and was found to have promising activity and acceptable tolerability in patients with relapsed MM. 49 Interestingly, weekly bortezomib combined with temsirolimus showed promising activity in relapsed MM, with responses in patients who had been refractory to prior bortezomib-containing regimens. 50 Since everolimus as a single agent showed promising activity, with a limited rate of side effects, in relapsed and/or refractory MM patients, efforts should be made to evaluate optimal combination partners to enhance the anti-myeloma activity and to target the PI3K-AKT-mToR signaling network at multiple sites.…”
mentioning
confidence: 99%
“…The results of early phase clinical trials utilizing mTOR inhibitors in MM have been modest thus far 32,33 . Pre-clinical studies have demonstrated improved efficacy using dual TORC1/2 inhibitors and by targeting feedback mechanisms, including the up-regulation of IGF1R phosphorylation and PI3K/AKT activation 3436 .…”
Section: Resultsmentioning
confidence: 99%
“…[122] in a Phase I/II study concluded that temsirolimus in combination with bortezomib may have a role in the treatment of relapsed or refractory MM without the addition of steroids. A Phase I study of everolimus in combination with lenalidomide drew a similar conclusion [123]. Recently, Li et al [124] extensively reviewed mTOR signaling as a therapeutic target in MM.…”
Section: Non-receptor Serine/threonine Kinase (S/tk) Inhibitorsmentioning
confidence: 87%